The effect of the pre-laboratory journal on the evaluating and designing scientific inquiry skills and socio-emotional of high school students - Nurul Melani; Tina Safaria Nilawati; Tri Suwandi (Assimilation: Indonesian Journal of Biology Education, 2023)
After over two years of the COVID-19 pandemic, learning policies demands adjustments from teachers and students, especially in practicum and scientific inquiry. To better prepare students for practicum, creating pre-laboratory journals is one approach. This study aimed to assess how pre-laboratory journals impact the development of scientific inquiry skills and socio-emotional growth in high school students. It used a quasi-experimental design with pretest-posttest control groups and selected participants through cluster random sampling. This study involved 70 students of 11th grade students consisting of 35 students of control class and 35 students of experimental class at Senior High School 1 Cisarua, West Bandung. The instrument used include five test that assessed and designed scientific inquiry skills related to the human excretory system, as part of the scientific literacy framework. The results revealed significant differences in the scientific inquiry skills between high school students in the experimental and control classes (p-value 0.00 0.05). The control class showed a moderate average improvement (N-gain of 0.53), while the experimental class exhibited a high average improvement (N-gain of 0.71). the control group was more anxious than the experimental group. Therefore, using pre-lab journals significantly improved both high school students' scientific skills and emotional well-being.